Learning to read while playing: The ludic as a significant resource in learning to read (Research, Society and Development, 2021)
Provoking a taste for reading in students has been a very difficult job. Why is it so difficult to make reading a meaningful process for elementary school students? How are methodologies worked in the classroom? Through these concerns we present in this article a work proposal for developing in a public school in Várzea Grande-MT, in Elementary School with 6th grade students, suggestions for some games and play and the importance of these significant pedagogical resources for learning to read and writing. The school makes little use of playful games in the practice of teaching and learning, and the absence of effective methods is now pointed out as the most important cause of the failure to teach reading. In this sense, the article aims to present alternatives in the teaching-learning process and build strategies that enhance the habit of reading through play and games to awaken the pleasure of reading in students and contribute to the formation of autonomous and competent readers. We carried out a descriptive and qualitative research and bibliographic nature with the studies of the authors exposed here, such as Santos (2001), Carvalho (2003), Fortuna (2018), Peixoto & Venturini (2021), among others. From this perspective, the aim of this work is to contribute to the teaching-learning of reading through play in a constructivist perspective, teaching in a relaxed and effective way based on theory and practice. The proposal contributed to a positive result in reading and writing process.